Functional performance study of an adapted design of the woman's condom: a crossover, noninferiority, randomized clinical trial. (4th May 2019) - Beksinska, Mags; Greener, Ross; Mphili, Nonhlanhla; Smit, Jenni; Kilbourne-Brook, Maggie; Coffey, Patricia S.
Abstract: Objectives: We aimed to assess the functional performance and safety of a modified Woman's Condom (WC2) against the existing FC2 female condom. Study design: This randomized clinical trial enrolled 287 women in one South African site. The primary outcome of the study was the rate of female condom failure. Participants were asked to use five of each female condom type and to collect information on use in a condom log at home and were interviewed after use of each FC type. Results: Noninferiority was demonstrated for the WC2 with respect to the reference condom FC2 for all condom functions. The WC2 was found to be superior to the FC2 reference condom for clinical failure ( p  = .000), total female condom failure ( p  = .001), misdirection ( p  = .000) and slippage ( p  = .004). Conclusion: The WC2 female condom performs as well as the FC2 female condom and offers good stability during use. Implications: Results from this study will inform further refinement of this female condom design, resulting in a new and potentially less expensive Woman's Condom.